Event marketing : how to successfully promote events, festivals, conventions, and expositions - Preston, Chris , 1961- (Hoboken, New Jersey : John Wiley & Sons, Inc, 2012)
A modern, completely updated guide to effective event marketing As the events market becomes increasingly saturated, it is essential for a successful event professional to understand the use of strategic marketing plans. Events are everywhere--in the U.S
1. What is an event and what is event marketing? -- 2. The evolution of event marketing -- 3. The theory and practice of event marketing -- 4. Sponsorship and cause-related event marketing -- 5. E-event marketing -- 6. Entertainment and festival event marketing -- 7. Corporate event marketing -- 8. Association, convention, and exhibition event marketing -- 9. Social event marketing -- 10. Future forces and trends in event marketing -- 11. Event marketing case studies
Includes bibliographical references (p. 273-293) and index
Keywords: Special events -- Marketing